Biophysical Characterization of (DOX-NPtm): FTIR and DSC Studies (JOURNAL OF ADVANCES IN PHYSICS, 2022)
Doxorubicin loaded into liposomes grafted with polyethylene glycol (PEG) has been demonstrated to have a longer circulation time and lower cardiotoxicity than doxorubicin (DOX). This study aims to investigate the biophysical characterization of a marketed formulation DOX-encapsulated liposome (DOX-NPTM). The interactions between doxorubicin and liposomal lipids can help in liposomal development. The liposome and DOX-NPTM were characterized in terms of differential scanning calorimetry (DSC) and Fourier transform infrared spectroscopy (FTIR). The rheological properties of liposomal samples were also measured. Physical interactions may be occurred between the drug functional groups and liposomal lipids, probably by weak hydrogen bond formation or weak bond formation due to dipole-dipole interaction. There was no shift of existing peaks or appearance of new peaks was detected between the characteristic peaks of the liposomal lipids were present in the DOX-encapsulated liposome sample. This suggests that there were physical interactions that took place only between the drug and lipids and no chemical interaction between them. DSC information shows that the phase transition temperature shifts to lower temperature degrees after loading of DOX into the liposomes. The DSC curve has a small broadening. This may infer a little cooperativity decrease between acyl chains of liposomal membranes after DOX inclusion. The encapsulation of DOX into liposomes decreases the plastic viscosity of liposomes (from 1.64 to 1.48 cP), which shows that the membrane ﬂuidity was increased.